An unusual mortality event in Johnstone River snapping turtles Elseya irwini (Johnstone) in Far North Queensland, Australia. Issue 10 (26th September 2017) - Ariel, E; Freeman, AB; Elliott, E; Wirth, W; Mashkour, N; Scott, J
Abstract : Background: An unusual mortality event in Johnstone River snapping turtles ( Elseya irwini ) in Far North Queensland, Australia, occurred during the summer months of December 2014 and January 2015. We report the data collected during the mortality event, including counts of sick and dead animals, clinical appearance and one necropsy. Outbreak description: Moribund animals appeared lethargic with variable degrees of necrotising dermatitis. Postmortem investigation of one freshly dead animal revealed bacterial and fungal involvement in the skin lesions as well as multifocal fibrinous hepatitis and splenitis and necrotising enteritis with vascular thrombosis. Aeromonas hydrophila was isolated from liver, spleen and skin lesions. All samples tested negative for ranavirus, and water and soil testing for environmental contaminants were negative. All affected E. irwini either died or were euthanased and no other species of animals in the river were affected. Conclusion: Aeromonas hydrophila is ubiquitous in the freshwater environment and although it caused septicaemia in the one individual that was submitted for laboratory diagnosis, the primary aetiology of the outbreak may not have been identified.